From wastewater to fertilizer products: Alternative paths to mitigate phosphorus demand in European countries. (December 2021) - Santos, Andreia F.; Almeida, Patrícia V.; Alvarenga, Paula; Gando-Ferreira, Licínio M.; Quina, Margarida J.
Abstract: Phosphorus (P) is a non-renewable resource, irreplaceable for life and food production, and currently considered a Critical Raw Material to the European Union (EU). Due to concerns about the rate of consumption and limited reserves in countries with sensitive geopolitical contexts, it is urgent to recover P from urban and industrial flows. Indeed, the municipal wastewater treatment plants (WWTP) are considered relevant sources with several hot spots, especially sewage sludge with estimated recovery efficiencies of >80%. The most promising recovery strategies are based on thermal treatments (e.g., incineration of sludge) following by wet-chemical or thermo-chemical leaching, precipitation, and adsorption. The direct application of sludge on soil is no longer a primary route for P reintegration in the value-chain for countries as Switzerland, Germany, and The Netherlands. In fact, Switzerland and Austria paved the way for implementing P recovery legislation, focusing on recovery from raw sewage sludge or ashes. Indeed, industrial technologies with sludge ash as input show high recovery efficiencies (Ashdec® and Leachphos® with 98 and 79%) and lower environmental impacts, whereas Pearl® technology has about 12% recovery efficiency with wastewater as input. After all, struvite emerges as the most recovered product with recent access to the internal market of EU fertilisers and similar growth performance compared to triple-super-phosphate. However, several studies leave open the possibility of introducing loaded adsorbents with P as soil amendments as a new alternative to conventional desorption. Briefly, P recovery should be a compromise between efficiency, environmental impacts, and economic revenues from the final products. Graphical abstract: Image 1 Highlights: Promising phosphorus (P) recovery spot is sewage sludge with efficiency >80%. The most advanced countries in P legislation are Switzerland and Austria. Sludge ash process reveals the best recovery efficiency. Struvite can compete with triple-super-phosphate fertiliser with similar performance. Direct application of an adsorbent loaded with P to the soil can be a new alternative.